Differentiated mouse kidney tubuloids as a novel in vitro model to study collecting duct physiology - Olde Hanhof, C. J. A.; Dilmen, E.; Yousef Yengej, F. A.; Latta, F.; Ammerlaan, C. M. E.; Schreurs, J.; Hooijmaijers, L.; Jansen, J.; Rookmaaker, M. B.; Orhon, I.; Verhaar, M. C.; Hoenderop, J. G. (Frontiers in Cell and Developmental Biology, 2023)
Kidney tubuloids are cell models that are derived from human or mouse renal epithelial cells and show high similarities with their in vivo counterparts. Tubuloids grow polarized in 3D, allow for long-term expansion, and represent multiple segments of the nephron, as shown by the gene expression pattern. In addition, human tubuloids form tight, functional barriers and have been succesfully used for drug testing. Our knowledge of mouse tubuloids, on the other hand, is only minimal. In this study, we further characterized mouse tubuloids and differentiated them towards the collecting duct, which led to a significant upregulation of collecting duct-specific mRNAs of genes and protein expression, including the water channel AQP2 and the sodium channel ENaC. Differentiation induced polarized expression of collecting duct water channels AQP2 and AQP3 and a physiological response to desmopressin and forskolin stimulation by translocation of AQP2 to the apical membrane. Furthermore, amiloride-sensitive ENaC-mediated sodium uptake was shown in differentiated tubuloids using radioactive tracer sodium. This study demonstrates that mouse tubuloids can be differentiated towards the collecting duct and exhibit collecting duct-specific function. This illustrates the potential use of mouse kidney tubuloids as novel in vitro models to study (patho)physiology of kidney diseases.